Análisis de las técnicas publicitarias empleadas por las marcas nido, pulp y kinder joy en el comportamiento de los niños de 4 a 6 años de la Alborada 10ma etapa de la ciudad de Guayaquil 2015 - Mora López, Lisbeth Johanna (2016)
This work has been developed in order to analyze the advertising techniques employed in Nido, Pulp and Kinder Joy brands and their influence on the behavior of children 4 to 6 years of age, specifically in the field of Alborada 10th stage of the city of Guayaquil, because it has been identified that from an early age children are exposed to various advertising content, perceived both media traditions such as tv, new technologies, as well as educational materials provided by the companies, the objective of creating go in small, consumer habit and preference to medium and long term for these products or brands. However, the problem lies mainly in advertising messages disseminated, which can cause changes in the behavior of children, this mainly attributed by the advertising techniques used where their age tend to accept and believe everything without taking into consideration as accurate as these messages……… ,